Compulsory Annuitisation: A Policy Option for Australia? - Taleitha O'Meara; Aaron Bruhn (Australasian Accounting, Business and Finance Journal, 2013)
The use of lifetime annuities is one obvious candidate to deliver guaranteed income in retirement. This paper quantifies the marginal increase in income to a single male when compelled to purchase a lifetime annuity from superannuation savings, compared to the current position of voluntary annuitisation in the Australian market. It is found that significant increases in average income are possible under compulsion, with an associated decrease in the cost of the age pension. Future mortality is shown to be the key area of sensitivity. The critical importance of future age pension eligibility rules being adaptable in line with mortality changes is demonstrated.
Keywords: Annuities; superannuation; compulsory annuitisation; retirement income; annuitization